Organic Semiconductors (MDPI - Multidisciplinary Digital Publishing Institute, 2015)
Over the last few years Organic Semiconducting industry showed significant growth in many areas dominated by conventional electronics. The foremost advantage of organic materials is that they are cheap, lightweight and flexible. In addition, the fabrication of organic materials from a defined molecular precursor using inkjet−printing technology is simple, bypassing the need for advanced semiconductor processing techniques. Organic thin films have already found confirmed and reliable applications in flexible displays, solar cells and biomedical applications, including implantable devices. Low cost materials, compatible with current organic electronic fabrication techniques and which improve device performance are in strong demand. This special issue of Organic Semiconductors covers Materials, Fabrication Techniques, Characterization, Devices and market adoption of Organic Semiconductors.